The impact of spatial frequency on hierarchical category representation in macaque temporal cortex - Esmaeil Farhang; Ramin Toosi; Behnam Karami; Roxana Koushki; Narges Kheirkhah; Farideh Shakerian; Jalaledin Noroozi; Ehsan Rezayat; Abdol-Hossein Vahabie; Mohammad-Reza A. Dehaqani (Communications Biology)
Abstract Objects are recognized in three hierarchical levels: superordinate, mid-level, and subordinate. Psychophysics shows that mid-level categories and low spatial frequency (LSF) information are rapidly recognized. However, the interaction between spatial frequency (SF) and abstraction is not well understood. To address this, we examine neural responses in the inferior temporal cortex and superior temporal sulcus of two male macaque monkeys. Our findings reveal that mid-level categories are well represented at both LSF and high SF (HSF), suggesting robust mid-level boundary maps in these areas, unaffected by SF changes. Conversely, superordinate category representation depends on HSF, indicating its crucial role in encoding global category information. The absence of subordinate representation in both LSF and HSF compared to intact stimuli further implies that full SF content is essential for fine-category processing. A supporting human psychophysics task confirms that superordinate categorization relies on HSF, while subordinate object recognition requires both LSF and HSF.